Weakly nonlinear boundary-value problems for Fredholm integral equations with degenerate kernel in Banach spaces - Zhuravlev, V.F. (Нелінійні коливання, 2018)
Weakly nonlinear boundary-value problems for Fredholm integral equations with degenerate kernel in Banach spaces are considered. We obtain necessary and sufficient conditions for finding solutions of these problems and construct converging iterative procedures of determination of solutions of these boundaryvalue problems.